2011
DOI: 10.1007/s10753-011-9400-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyranocoumarins Isolated from Peucedanum praeruptorum Dunn Suppress Lipopolysaccharide-Induced Inflammatory Response in Murine Macrophages Through Inhibition of NF-κB and STAT3 Activation

Abstract: Praeruptorin C, D, and E (PC, PD, and PE) are three pyranocoumarins isolated from the dried root of Peucedanum praeruptorum Dunn of Umbelliferae. In the present study, we investigated the anti-inflammatory effect of these compounds in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophage cells. Pyranocoumarins significantly inhibited LPS-induced production of nitric oxide, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). The mRNA and protein expressions of inducible nitric oxide synthase, IL-6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…To investigate whether the inhibition of inflammatory response by mollugin is mediated through the MAPKs pathway, MAPKs phosphorylation was examined by Western blot in RAW264.7 cells pretreated with mollugin and then with LPS according to the published method. 16) As shown in Fig. 4, mollugin did not suppress the lPS-stimulated phosphorylation of ErK1/2, p38, and JNK1/2.…”
Section: Cytotoxicity Of Mollugin On Raw2647 Cellsmentioning
confidence: 67%
“…To investigate whether the inhibition of inflammatory response by mollugin is mediated through the MAPKs pathway, MAPKs phosphorylation was examined by Western blot in RAW264.7 cells pretreated with mollugin and then with LPS according to the published method. 16) As shown in Fig. 4, mollugin did not suppress the lPS-stimulated phosphorylation of ErK1/2, p38, and JNK1/2.…”
Section: Cytotoxicity Of Mollugin On Raw2647 Cellsmentioning
confidence: 67%
“…Phytochemical and pharmacological studies showed that angular-type pyranocoumarins are the major constituents of this plant [3][4][5][6][7][8][9], and these compounds have various beneficial effects such as anti-inflammatory [10][11][12], antiasthma [13], chemopreventive [14], smooth muscle relaxant [15], neuroprotective [16], and anti-osteoclastogenic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the isolates were determined spectroscopically using one-dimensional (1D)-and two-dimensional (2D)-nuclear magnetic resonance (NMR) analysis. All the compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were evaluated for multidrug resistance (MDR) reversal and anti-inflammatory activity against multidrug resistant MES-SA/Dx5 cancer and lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Here, we 1 Hz, H-4′′′), 1.81 (3H, m, H-5′′′)] were observed from the 1 H-NMR spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage is a type of immune cells that plays a critical role in immune responses, host defense, and tissue repair. This cell type produces various pro-inflammatory mediators such as tumor necrosis factor-alpha (TNF-a) and IL-6, as well as several inflammatory mediators such as NO and prostaglandin E 2 (PGE 2 ) when treated with LPS (Yu et al 2012). RAW 264.7 cell line has been demonstrated as a good model to conduct studies on inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%